THE DISTINCTION BETWEEN THE CONCEPTS OF “SPEECH CULTURE” AND “LANGUAGE CULTURE”, “SPEECH CULTURE” AND “SPEECH CORRECTNESS” - Usmanova Svetlana Negmatovna (Scholar Express Journals, 2026)
The article examines the differences between the concepts of “speech culture,” “language culture,” and “speech correctness.” Based on an analysis of domestic linguistic research, it is determined that language culture is a system of norms related to the language system as such, whereas speech culture includes the communicative, ethical, and social aspects of speech. Speech correctness is considered one of the components of speech culture, reflecting the compliance of an utterance with the norms of the literary language. The article emphasizes that speech culture is a broader concept that encompasses correctness, expressiveness, appropriateness, and ethicality of utterances. Practical recommendations are provided for the development of speech culture in the educational environment.
Keywords: Speech culture; language culture; speech correctness